Best Animation: 8 & Halfilm Awards: Special Cannes Film Festival Event - Sofokleous, Konstantina (My University, 2026)
'Tin Box' 8 & Halfilm Awards: Special Cannes Film Festival Event, France
Keywords: Arts and entertainment